2008
DOI: 10.1143/apex.1.061602
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and Piezoelectric Properties of Mn-Doped Na0.5K0.5NbO3Single Crystals Grown by Flux Method

Abstract: Lead-free piezoelectric Mn-doped Na 0:5 K 0:5 NbO 3 (NKN) single crystals have been fabricated by self flux method using KF-NaF eutectic composition. The color of the obtained crystals was different depending on the doped Mn-chemicals. The large-sized single crystals with crystal face of orthorhombic (110) were obtained by optimized heat-treatment condition of the holding time at 1050 and 950 C of 5 h and the cooling rate of 0.25 C/min, and their piezoelectric properties were successfully measured by a resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 18 publications
0
45
2
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] In order to further enhance the piezoelectric properties, different dopants, such as Li þ , Ta 5þ or single crystal growths have been considered, [3][4][5][6][7] in which the 0.5%MnO 2 -(K 0.5 Na 0.5 )NbO 3 (Mn-KNN) single crystals show higher piezoelectric/dielectric properties than those of pure (K 0.5 Na 0.5 )NbO 3 material, with comparable orthorhombic to tetragonal phase transition temperature and Curie temperature. [8][9][10][11][12] Domain size engineering is another important approach for obtaining enhanced piezoelectric properties in lead free piezoelectric single crystals. [13][14][15][16][17][18] The experimental results revealed that the enhanced piezoelectric coefficient was associated with high domain wall density, for example, the piezoelectric coefficient d 31 was found to increase from À98 pC/N to À230 pC/N with domain sizes of 40 lm and 5.5 lm in BaTiO 3 crystals, 15 while the piezoelectric coefficient d 33 was predicted to be greatly increased with nano-size domain configuration.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] In order to further enhance the piezoelectric properties, different dopants, such as Li þ , Ta 5þ or single crystal growths have been considered, [3][4][5][6][7] in which the 0.5%MnO 2 -(K 0.5 Na 0.5 )NbO 3 (Mn-KNN) single crystals show higher piezoelectric/dielectric properties than those of pure (K 0.5 Na 0.5 )NbO 3 material, with comparable orthorhombic to tetragonal phase transition temperature and Curie temperature. [8][9][10][11][12] Domain size engineering is another important approach for obtaining enhanced piezoelectric properties in lead free piezoelectric single crystals. [13][14][15][16][17][18] The experimental results revealed that the enhanced piezoelectric coefficient was associated with high domain wall density, for example, the piezoelectric coefficient d 31 was found to increase from À98 pC/N to À230 pC/N with domain sizes of 40 lm and 5.5 lm in BaTiO 3 crystals, 15 while the piezoelectric coefficient d 33 was predicted to be greatly increased with nano-size domain configuration.…”
Section: Introductionmentioning
confidence: 99%
“…The KNbO 3 -NaNbO 3 system has a morphotropic phase boundary close to the (K 0.5 Na 0.5 ) NbO 3 composition and it has to replace PZT, then the electrical properties of KNN have to be improved Piezoelectric single crystals have attracted much for their varied applications such as medical transducers and sonar, as they possess high piezoelectric constants and high electromechanical coupling factors [1,2].In this work, we have studied the lead-free Na 0.5 K 0.5 NbO 3 (KNN) piezoelectric single crystals [3,4] as most of the lead based piezoelectric materials are toxic. The KNN has a high Curie temperature and a large piezoelectric coefficient [5].…”
Section: Introductionmentioning
confidence: 99%
“…The highest resistivity is achieved in the Mn-KNN crystal grown by flux method and annealed at 1,100 C in an air atmosphere which shows a well-saturated hysteresis loop with a remanent polarization of 40 mC cm À2 and coercive field of 12 kV cm À1 [65]. KNN crystals by flux method have also been grown by some other groups [69,71,73]. Figure 5.8 shows the P-E hysteresis loop of a 0.5 mol% Mn-doped KNN single crystal grown by the flux method with remnant polarization of 52 mC cm À2 which is one of highest values reported for KNN-based materials [71].…”
Section: Knn-based Single Crystalsmentioning
confidence: 99%